Impact of parathyroidectomy on inflammatory and cardiovascular risk parameters in primary hyperparathyroidism: a retrospective analysis - Nese Bulbul; Suat Sen; Fettah Acibucu (BMC Cardiovascular Disorders)
Abstract Background Parathyroidectomy has been shown to reduce cardiovascular risk factors in some studies, although findings on these parameters remain inconsistent. Objectives This study aimed to evaluate inflammatory and cardiovascular risk markers in patients with Primary Hyperparathyroidism (PHPT) before and one month after successful parathyroidectomy (PTX). Methods We retrospectively analyzed PHPT patients who visited the outpatient clinic between 2015 and 2020. Patient demographics, hemogram data, calcium, parathormone (PTH), vitamin D, high-density lipoprotein (HDL), mean platelet volume (MPV), neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), and monocyte-to-HDL ratio (MHR) were recorded and compared pre- and postoperatively. Results The analysis revealed significant postoperative increases in platelet, MPV, HDL, PLR, and vitamin D levels (p = 0.001, p = 0.001, p = 0.001, p = 0.024, p = 0.001, respectively). Conversely, PTH, calcium, NLR, and MHR levels significantly decreased (p = 0.001, p = 0.001, p = 0.011, p = 0.019, respective-ly). Correlation analysis demonstrated a negative association between postoperative PTH and vitamin D (p = 0.010, r = -0.292**) and a positive association between postoperative PTH and both calcium (p = 0.008, r = 0.309**) and NLR (p = 0.046, r = 0.227**). Multivariable regression analysis demonstrated that postoperative PTH levels were significantly associated with calcium (B = 39.82, Beta = 0.321, p = 0.0469), NLR (B = 110.02, Beta = 0.428, p = 0.0384), baseline comorbidity scores (B = -30.54, Beta = -0.287, p = 0.0361), and preoperative inflammation levels (B = 25.69, Beta = 0.311, p = 0.0386). Conclusion Our findings highlight a potential link between PHPT and inflammatory-cardiovascular risk, with parathyroidectomy exerting a beneficial effect within the first month post-surgery. The study also suggests that these risk factors may be modifiable with timely surgical intervention. Clinical trial number Not applicable.